Antibiogram of Escherichia coli and Staphylococcus aureus Isolated from Milk Sold in Kathmandu District - Rai, Shyamala; Karki, Barsha; Humagain, Sujita; Rimal, Sandesh; Adhikari, Sandhya; Adhikari, Shilpa; Thapa, Suchitra (Nepal Journal of Biotechnology, 2020)
The emergence of antibiotic resistance in microorganisms and the presence of such isolates in milk pose a great risk to public health. Therefore, this study aims to determine the antibiotic susceptibility pattern of Escherichia coli and Staphylococcus aureus isolated from milk and assess the microbial quality of milk. For this, a total of 70 milk samples were collected and the total bacterial count (TBC) was determined. E. coli and S. aureus were isolated using their respective selective media while antibiotic susceptibility testing was carried out by Kirby Bauer Disc Diffusion method. The TBC showed that the raw milk samples contained two-fold higher microbial load while the pasteurized milk samples contained four-fold higher microbial loads than the standard guidelines. A total of 62 isolates were identified from culture-positive milk samples of which 32 were E. coli and 30 were S. aureus. A significant correlation was observed between microbial load and the organism isolated (r = 0.339, p